Risk of childhood overweight or obesity associated with excessive weight gain during pregnancy: a meta-analysis - Tie, Hong-Tao; Xia, Yi-Yin; Zeng, Yong-Sheng; Zhang, Yong; Dai, Chia-Liang; Guo, Jeff Jianfei; Zhao, Yong (Archives of gynecology and obstetrics, 2014)
Purpose Several investigations have shown that the risk of childhood overweight and obesity may be associated with excessive gestational weight gain (GWG), but the study samples were limited and results were mixed; hence we conducted this meta-analysis to assess the explicit association between them and present evidence. Methods We searched PubMed, EMbase, Ovid, Web of knowledge and Cochrane library for relevant studies. Bibliographies from retrieved articles were also manually searched. Cohort studies that presented results by OR or RR with 95 % CI for the association of maternal excessive GWG and child overweight/obesity were included. The pooled estimates were calculated by fixed-effect model or random-effect model according to the heterogeneity. Results Twelve cohort studies were identified, and the combined OR of excessive GWG and childhood overweight/obesity was 1.33 (95 % CI 1.18–1.50) with evidence of heterogeneity ( P = 0.000, I 2 = 71.1 %). Adjustment of maternal BMI, investigation area, age of children, research type, and omission of any single study had little effect on the pooled estimate. After eliminating the effect of publication bias by trim and fill analyses, the result still remained statistically significant (OR 1.21, 95 % CI 1.05–1.40). Conclusions This meta-analysis suggests that the risk of childhood overweight/obesity is significantly associated with excessive gestational weight gain.